RANCANG BANGUN APLIKASI REKRUTMEN & SELEKSI BERDASARKAN KOMPETENSI PADA PT. TUNGGAL DJAJA INDAH - Kristianto S.Kom., Dimas Dewa; S.Si., M.M., Sulistiowati; Maulana S.Kom., Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: PT. Tunggal Djaja Indah (PT. TDI) is a leading paint manufacturer in Indonesia. ISO 9001 which has obtained by PT. TDI is a proof of the seriousness of the company. To support that business, the company requires recruitment and selection processes which aim to get a competent human resources. Based on observations and interviews, the company has difficulties to selecting applicants although they has structured competency standards. The company spend a lot costs that used for recruitment process and they needs a long time to execute multiple processes in accordance with company SOPs. To overcome these problems, PT. TDI needs an application of recruitment and selection based on competency. This application can produce the form of interviews based on competency, reduce cost of telephone and streamline the recruitment and selection processes. Thus, it is expected that the outcome of the application can provide list of candidates who are competent to HRD Manager.